Large-Scale Evaluation of Indonesian Elite Maize Breeding Lines for Resistance Against Bacterial Stalk Rot Caused by Dickeya zeae - Devi Mienanti; Iqbal Hidayat; Yanuar Danaatmadja; Mohammad Bahrelfi Belaffif; Budi Waluyo; Arifin Noor Sugiharto; Ajay Goel Kumar; Kuswanto Kuswanto (AGRIVITA Journal of Agricultural Science, 2024)
Bacterial stalk rot is one of the important diseases in maize caused by Dickeya zeae. Infection of this disease can lead to a considerable amount of loss in yield, with up to 98 percent loss of yield. The use of resistant materials is the most effective approach to managing bacterial stalk rot in maize. This study evaluates a large-scale phenotypic screening of 624 maize lines against bacterial stalk rot, divided into two groups based on a heterotic pool. These lines are used in a commercial breeding program in Indonesia. This study develops a stabbing method with a large gauge hypodermic needle, allowing for scalability in delivering inoculum while performing large-scale line evaluation. The result from ANOVA reveals a significant (P<0.05) effect of lines, day after infection, and interaction between day after infection and group. Group two displays fewer resistant lines compared to group one. This work presents a method for large-scale line evaluation for resistance against bacterial stalk rot, where the information obtained can be used in industrial breeding programs for routine material screening during the development of new lines or hybrids and for genomic studies of bacterial stalk rot resistance.